From Classroom to Cloud : Radiology Education in a Post-Pandemic Era - Yew, Ting Ting; Cheah, Whye Lian; Ahmad Tirmizi, Jobli; Koa, Ai Jiun; Nariman, Singmamae (2024)
Background: The COVID-19 pandemic necessitated a shift from traditional face-to-face learning to online and blended learning modalities in medical education. This study aims to evaluate the effectiveness of online learning compared to blended learning in radiology education among medical students.